Kecintaan Batik Daerah Sebagai Tren Fashion Budaya Masyarakat Kuantan Singingi - Yuliantoro; Iqbal Septama Yuda; Hafif Zulkhairi; Nabila; Alya Putri Meirinda; Tasya Amajirah; Zulpines Indira Putri; Wahyu Ningsih; Nadia Handayani; Walzumni; Azhari Resta Eriansa (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Batik is a cultural heritage of Indonesian traditional artwork that has been recognized worldwide. Almost every region in Indonesia has regional batik that has its own characteristics, including Kuantan Singingi Regency. Batik Kuansing through the love of regional batik can be developed into a fashion trend that contains cultural values of the community. From this reason the author describes a little how efforts are made as a form of love for regional batik so that it can develop into a cultural fashion trend of the Kuantan Singingi community. the method used is a qualitative approach in collecting sources through observation, interviews, and literature related to the love of regional batik as a cultural fashion trend of the community. The purpose of this article is to review and find out more about how the form of love for regional batik as a cultural fashion trend of the Kuantan Singingi community will be published as general information to provide broad public knowledge. As a result, Batik Kuansing as a regional batik can develop into a cultural fashion trend of the community. This can be realized if all parties, namely, the community, the younger generation, the local government, and the batik KUB can work together by making efforts to increase the love of regional batik and cultivate the use of regional batik so that it develops into a cultural fashion trend of Kuantan Singingi society.